In vitro dose measurements in a human cadaver with abdomen/pelvis CT scans. Issue 9 (26th August 2014) - Zhang, Da; Padole, Atul; Li, Xinhua; Singh, Sarabjeet; Khawaja, Ranish Deedar Ali; Lira, Diego; Liu, Tianyu; Shi, Jim Q.; Otrakji, Alexi; Kalra, Mannudeep K.; Xu, X. George; Liu, Bob
Abstract : Purpose: : To present a study of radiation dose measurements with a human cadaver scanned on a clinical CT scanner. Methods: : Multiple point dose measurements were obtained with high‐accuracy Thimble ionization chambers placed inside the stomach, liver, paravertebral gutter, ascending colon, left kidney, and urinary bladder of a human cadaver (183 cm in height and 67.5 kg in weight) whose abdomen/pelvis region was scanned repeatedly with a multidetector row CT. The flat energy response and precision of the dosimeters were verified, and the slight differences in each dosimeterˈs response were evaluated and corrected to attain high accuracy. In addition, skin doses were measured for radiosensitive organs outside the scanned region with OSL dosimeters: the right eye, thyroid, both nipples, and the right testicle. Three scan protocols were used, which shared most scan parameters but had different kVp and mA settings: 120‐kVp automA, 120‐kVp 300 mA, and 100‐kVp 300 mA. For each protocol three repeated scans were performed. Results: : The tube starting angle (TSA) was found to randomly vary around two major conditions, which caused large fluctuations in the repeated point dose measurements: for the 120‐kVp 300 mA protocol this angle changed from approximately 110° to 290°, and caused 8% − 25% difference in the point dose measured at the stomach, liver, colon, and urinary bladder. When the fluctuations of the TSA were small (within 5°), the maximum coefficient of variance was approximately 3.3%. The soft tissue absorbed doses averaged from four locations near the center of the scanned region were 27.2 ± 3.3 and 16.5 ± 2.7 mGy for the 120 and 100‐kVp fixed‐mA scans, respectively. These values were consistent with the corresponding size specific dose estimates within 4%. The comparison of the per‐100‐mAs tissue doses from the three protocols revealed that: (1) dose levels at nonsuperficial locations in the TCM scans could not be accurately deduced by simply scaling the fix‐mA doses with local mA values; (2) the general power law relationship between dose and kVp varied from location to location, with the power index ranged between 2.7 and 3.5. The averaged dose measurements at both nipples, which were about 0.6 cm outside the prescribed scan region, ranged from 23 to 27 mGy at the left nipple, and varied from 3 to 20 mGy at the right nipple over the three scan protocols. Large fluctuations over repeated scans were also observed, as a combined result of helical scans of large pitch (1.375) and small active areas of the skin dosimeters. In addition, the averaged skin dose fell off drastically with the distance to the nearest boundary of the scanned region. Conclusions: : This study revealed the complexity of CT dose fluctuation and variation with a human cadaver.